Takhreej e-Guide: an innovation of electronic guide for Takhreej Al-Isnad Al-Hadith-based on physical structure of Isnad and principles of Hadith science - Ibrahim, Nuzulha Khilwani; Ahmed Ali, Ahmed El-Mogtaba Bannga; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Kartiwi, Mira; Hasan Basari, Abdul Samad (Centre for Global Open Access Learning - Immersive Technology & Quality Assurance (GOAL-ITQAN), Universiti Sains Islam Malaysia (USIM), 2017)
Highlights:  Takhreej is one of processes to examine hadith’s authenticity. ‘Takhreej e-Guide’ is an electronic guide to Takhreej the Isnad of Hadith.  Nowadays, Takhreej Hadith has also been widespread to the syllabus for secondary school curriculum, NOT ONLY for undergraduate students in Higher Learning Education as it before.  There is a list of websites in Arabic available for Takhreej purpose, but SURPRISINGLY, there is no website found to provide an electronic guide to do Takhreej step-by-step, for the new beginner in this study, especially the non-Arab speakers.  From there, the idea to produce this guide is triggered.